Desenvolvimento de eletrodo impresso utilizando tinta condutiva e deposição por sputtering - Silva Neto, João Afonso da (2019)
This work deals with the development of a methodology for the construction of printed electrodes, using vinyl adhesives as mold for the construction of electrodes. Using this innovative methodology was constructed printed electrodes (EI), and electrodes constructed by sputteting (SPT). For the EI, carbon conductive paint was used in the preparation of the working electrodes and counter electrode, a silver conductive ink was used in the preparation of the reference electrode, resulting in the electrode EI-Ag (printed electrode whose reference is silver) . A second EI was constructed starting from the EI-Ag, the EI-Ag / AgCl (printed electrode whose reference electrode is silver / silver chloride). Using the same adhesive design used for the construction of the above electrodes, the so-called SPT-Au-Ag electrodes were constructed, this one has the work electrode and conter electrod made in gold, which were constructed by sputtering. The morphology of the electrodes was analyzed by stereomicroscopy, scanning electron microscopy and atomic force microscopy. The three electrodes developed in this work were compared to a commercial electrode of Dropsens DS110. The electrochemical profiles were evaluated and compared by cyclic voltammetry, using the reversibility diagnostics, using the cationic probe ferrocyanide and ferricyanide. It is still evaluating the repeatability for the current values for the same probe as well as the current density values. Using the SPT-Au-Ag electrode, initial tests were performed aiming the construction of a MicroRNA-184 biosensor, and this is of great relevance for the diagnosis and / or monitoring of carcinogenic pathologies.